PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT BPR MARCORINDO PERDANA TANGERANG SELATAN - Abdul Rohmanilah; Ali Zaenal Abidin (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of work discipline and motivation, both partially and simultaneously, on employee performance at PT BPR Marcorindo Perdana with a sample of 60 employees. The method used is a quantitative method. The data analysis used in this research is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that work discipline has a significant effect on employee performance in the Y regression = 2.267 + 0.947 Motivation has a significant effect on employee performance with the regression equation Y = 12.958+ 0.639 Work Discipline and Motivation simultaneously have a significant effect on Employee Performance with the regression equation Y = 11.547+ 0.248 X1 + 0.458 X2. The coefficient of determination value was 88.5%, while the remaining 11.5% was caused by other variables not examined in this research. The test results for the first hypothesis obtained a calculated t value > t table or (11.832 > 2.002). Based on the results of testing the second hypothesis, the calculated t value > t table or (7.675 > 2.002) is obtained. Based on the results of testing the third hypothesis, the calculated F value was 219.244 > F table 3.159. This shows that simultaneously the work discipline and motivation variables have a significant influence on employee performance.